ANALISIS FRAMING PAN DAN KOSICKI TERHADAP KASUS SALIM KANCIL PADA KOMPAS TV DAN TV ONE - Resmiati, Erni; Rochim, Achludin Ibnu; Widiyanto, Kendry (representamen, 2017)
Television became a media that hit the hearts of people and still the media with the most audience.Excess television is audiovisual. This means that television can combine sound and moving imagesthat can attract the attention of the audience. The lack of television lies in the nature of the transistorso that it is only momentary or fleeting. This study aims to analyze the point of view of both journalistsTV One and Kompas TV in framing the news case Salim Kancil. So that can be seen from theperspective of each journalist and media decisions in reporting information coverage. Framinganalysis is done with Pan and Kosicki analysis model with a qualitative approach. The results showedthat Framing Tv one against the event of a mouse deer into an excessive emphasis so that aconventional event with a long duration and Compass Tv still with a reasonable dose in meeting theneeds of the community in obtaining information.Keywords: Analysis, Framing, Pan and Kosicki, Salim Kancil, Media Kompas TV, TV One.